Gene-modified genotype II live attenuated African swine fever virus induces cross-protection against genotype I but not against genotype IX - Rathakrishnan, A.; Hemmink, Johanneke D.; Petrovan, V.; Reis, A.L.; Dixon, L.K. (Informa UK Limited, 2025)
African swine fever virus originated in a wildlife cycle in East Africa and spread to domestic pigs. At least twenty-three genotypes are present in Africa whereas only genotypes I and II have spread to other continents. Vaccine development has been directed mainly to genotype II. The ability of genotype II vaccines to induce cross-protection against other genotypes is unknown. Here, we compared cross-protection induced in pigs by an attenuated multiple gene-deleted genotype II modified live vaccine candidate against challenge with different genotypes. Protection against homologous virulent genotype II virus was 100%. Cross-protection against virulent genotype I virus varied between 57 and 71%. However, no protection was achieved against genotype IX challenge. The results indicate potential for use of vaccines in regions where genotypes I and II are circulating.